Development of Islamic Education Learning Tools Based on E-Learning to Enhance Students Digital Literacy - Muchlis Muchlis; Gunawan Gunawan; Muhammad Irwansyah; Magfirah Perkasa; Erni Suryani (Universitas Pendidikan Mandalika (UNDIKMA), 2022)
The purpose of this research is to develop islamic education learning tools based on e-learning that valid, practical and effective to use. The type of research is research and development by adopting the Thiagarajan development model, which consists of 4 stages, namely defining, designing, developing and disseminating. The research instruments used in this study were validation sheets and learning outcomes tests using the Jamboard application. Analysis of the data used in this study (1) By conducting a feasibility analysis on the e-learning learning module, Student Activity Sheet (LKM) and student learning outcomes tests. Based on the results of the validation, the overall learning tools in the form of e-learning modules for Islamic religious subjects, LKM and learning outcomes tests are generally declared valid. The details of the module validation scores are generally very valid (M = 3.62), the LKM is generally declared valid (3.31) and the learning outcomes test is declared to be (M = 3.43). (2) conducting trials on e-learning and LKM learning modules. The learning tools developed can be said to be valid because the development process is based on a strong theoretical rationale and has internal consistency so that the teaching materials have high reliability and consistency, so that it can be used to enhance students’s digital literacy.